دراسـة بعض الخواص الميكانيكية لمـتراكب Epoxy-MgO - الراوي خالد رشاد; سلمان رفقة عامر (Al-Nahrain Journal of Science, 2018)
In this study a polymeric composite material was prepared by hand- layup technique from epoxy resin as a matrix and magnesium oxide as a reinforcement with ratio (0%, 5%, 10%, 15%, 20%, 25%) to resin. Three point bending testing & Hardness testing were investigated and the results illustrate the bending elastic modulusis improved and the hardness increasing with (MgO) concentration increase.